78‐1: Correcting Metameric Failure of Wide Color Gamut Displays. Issue 1 (30th May 2018) - Bodner, Ben; Robinson, Neil; Atkins, Robin; Daly, Scott
Abstract : When calibrating wide‐gamut displays, a colorimetric match may result in perceived color error due to inaccuracies of the CIE 1931 observer. In this study, methods of correcting values measured on wide gamut displays to perceptually equivalent values on standard gamut displays were analyzed using visual color matching data.